Mathematical and computational methods in physiology : satellite symposium of the 28th International Congress of Physiological Sciences, Budapest, Hungary, 1980 - Fedina, L. (International Congress of Physiological Sciences (28th. 1980 : Budapest, Hungary). Advances in physiological sciences ;, 1981)
Mathematical and Computational Methods in Physiology.